Verniz à base de quitosana contendo própolis verde brasileira: avaliação da atividade antimicrobiana, citotoxicidade e perfil de liberação - Mariana Passos de Luca (2011)
Varnishes are formulations that, when associated with antimicrobials, are being used in Dentistry to control and prevent cariogenic biofilm. In this context, chlorhexidine is the gold standard in antimicrobial varnishes, although chlorexidine has some side effects affecting taste and oral mucosa. The aim of this work was to develop a polymeric varnish containing chitosan and Brazilian green propolis to control and prevent cariogenic biofilm, considering that propolis has been demonstrating antimicrobial activity against oral pathogenic bacteria in several studies worldwide. To the chitosan polymeric varnish was added green propolis ethanolic extract in different concentrations: varnish A (15% green propolis ethanolic extract/GPEE), varnish B (10% GPEE), varnish C (5% GPEE), varnish D (7, 5% GPEE), varnish E (5% GPEE), varnish F (10% GPEE), varnish G (5% GPEE). The antimicrobial activity was tested according to CLSI (2007) patterns and carried out against standard samples of Streptococcus mutans and Streptococcus sanguinis through agar diffusion method. Results were obtained through the mean size of the inhibiting halo and their deviation standards, which showed that all the varnishes inhibited both bacteria, but in 24 hours, varnish B formed the biggest halo at S. mutans (8,92±0,68), while varnish A formed the biggest halo at S. sanguinis (10,91±0,79) at the same period. After 48 hours, varnish F formed the biggest halo at S. mutans (9,53±1,07) and varnish A formed the biggest halo at S. sanguinis (10,23±0,35). The cytotoxicity test with osteoblasts was made according to the ISO 100993-5 patterns and the cellular viability was accessed through the MTT essay, which demonstrated that all the varnishes kept 80% of the viable cells, showing low cytotoxicity and presenting significative statistical difference with the varnish base containing just chitosan, which allowed cellular proliferation (120%). The sustained-release test was carried out after the aplication of 40 µL of each varnish in the enamel surface of bovine teeth and kept in ethanol/water solution in regular times. Results showed that, in therms of immediate liberation, next to 8 hours, the best performance was observed in the varnishes E and F; mean performance was reached by the G and A varnishes; and the worst performance was observed in the C, D and B varnishes.The best prolonged performance was made by varnish A. These results allow us to conclude that the varnish containing chitosan and Brazilian green propolis has potencial to be applied clinically in the prevention and control of cariogenic biofilm, considering that the formulation of the varnish A, containing 15% of the green propolis ethanolic extract, gave the best results in all the applied tests.